Performativity: enrollments, contexts, dissemination (Práxis Educativa, 2014)
The term performativity and its inflexions have been applied to several concepts in the field of educational research. In this study, we trace the dissemination of the word performativity and its correlates, starting from the meanings attributed to the term by Stephen Ball, in his analysis of contemporary educational policies, but also using the theories of Jacques Derrida and Judith Butler, who used these terms to refer to social processes of signification and identification, and also references made to the term in studies of Anthropology, Arts, Political Science, Linguistics, Philosophy and Physics. On top of that, we researched studies in the field of academic education, examining articles from journals and other periodicals published over the last five years, in order to discuss the various meanings attributed to the term within the educational field. We present, in this paper, a synthesis of our investigations, highlighting the affirmations, negations and truth effects that can be construed from the use of these terms in educational research, in particular when approaching current educational policies. Keywords: Performativity. Educational policies. Iterability.